PHARMACEUTICAL PROPERTIES OF VENOM TOXINS AND THEIR POTENTIAL IN DRUG DISCOVERY - Jeroen Kool (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Traditional pipelines feeding drugs coming to the market are declining. This is one of the reasons why nowadays the previously abandoned natural extract drug discovery programs are slowly coming back. In this scenario, small molecular metabolites from plants and single cell marine or soil organisms are gaining interest in pharmaceutical research again. Animal venoms are another source for finding new biopharmaceutical lead molecules and research interest in discovering bioactive molecules from venoms is rising. Venoms comprise often highly selective and potent bioactive peptides and small proteins for receptors and enzymes that are valid drug targets. This work discusses drug discovery research on bioactive compounds in venoms and gives older and more recent examples of bioactive compounds found in venoms from different animals. Common pharmaceutical targets that different classes of venom toxins interact with and information on developmental stages of several medicinal venom peptides are also discussed. Key words:venom, toxin, drug discovery, peptide, pharmaceutical activity